Созологічна оцінка рідкісних видів рослин зональних екосистем на території басейну р. Ворскла (Україна, Російська Федерація) - Bayrak, O.M.; Shaparenko, I.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The article presents the results of sozological assessment of rare plant species of zone ecosystems and river Vorskla basin. 121 plant species are clasified into phytosozological categories. The analysis of the nature preserve fund’s structure in the observed area and the sozological description is given.